Differentiating knowledge transfer and technology transfer: What should an organizational manager need to know? - Ismail, Maimunah; Hamzah, Siti Raba'ah; Bebenroth, Ralf (Emerald, 2018)
Purpose: The purpose of this paper is to examine the conceptualization of knowledge transfer and technology transfer to seek answers to the question: Why should an organizational manager need to know the difference between knowledge transfer (KT) and technology transfer (TT)? Design/methodology/approach: An extensive literature review method was used to identify and analyze relevant international publications. The literature sources are categorized as follows: literature on KT only, literature on TT only and literature on comparative analysis on KT and TT. The conceptualization of KT and TT is based on signaling theory. Findings: The authors identified differences between KT and TT based on six dimensions, namely knowledge versus technology characteristics, usage of KT and TT in national development, sender versus receiver, intra-firm versus inter-firm transfer, foreign direct investment (FDI) and workers’ mobility. Research limitations/implications: This is a conceptual analysis that should contribute to the existing literature by comprehensively reviewing the processes of KT and TT based on selected research conducted worldwide as well as suggest practical guidelines to organizational managers in managing KT and TT. Originality/value: This review could shed new insights for future researchers to validate and examine the identified differences between KT and TT so that managers could make use of the findings to manage KT and TT successfully in their organizations.